One‐way endobronchial valves in the management of complex persistent air leaks in a soft tissue sarcoma patient - Alfonso Fiorelli; Lucia Cannella; Francesca Capasso; Antonio Pizzolorusso; Feranda Picozzi; Gaetana Messina; Giovanni Natale; Edoardo Mercadante; Salvatore Tafuto (Thoracic Cancer, 2023)
Abstract Complex persistent air leak (PAL) is a clinical condition which is difficult to treat. Herein, we report the clinical case of an 18‐year‐old woman with lung and bone metastases due an ultrarare sarcoma: “round cell sarcoma non‐Ewing”. She developed persistent air leaks due to an alveolopleural fistula which developed following two cycles of chemotherapy with doxorubicin. Chest drainage with suction failed to resolve the air leaks, while surgical treatment was unfeasible due to the poor clinical condition of the patient. Thus, she was reviewed for endoscopic treatment with one‐way endobronchial valves. A small valve was sequentially inserted within each segment of the right upper bronchus to occlude the entire upper lobe. Two days after the procedure, resolution of the air leaks were obtained. Chest drainage was removed 5 days later and the patient was discharged. Chemotherapy was resumed. The patient died 7 months later because of disease progression.